Sedentary Lifestyle of Older Adults and Its Associated Factors: A Multicentre Cross-Sectional Study During COVID-19 Pandemic in Indonesia - Siti Setiati; Kuntjoro Harimurti; Ika Fitriana; Noto Dwimartutie; Rahmi Istanti; Muhammad Khifzhon Azwar; I Gusti Putu Suka Aryana; Sri Sunarti; Agus Sudarso; Dina Aprillia Ariestine; Lazuardhi Dwipa; Novira Widajanti; et al. (Acta Medica Indonesiana)
Background: COVID-19 is here to stay, and humans ought to decide how to adapt. We aimed to describe lifestyle changes during COVID-19 pandemic, and to determine the prevalence and factors associated with sedentary lifestyle among older adults.